North–south pathways, emerging variants, and high climate suitability characterize the recent spread of dengue virus serotypes 2 and 3 in the Dominican Republic - Miguel, Isaac (2024)
Background: Dengue fever remains a significant public health challenge in tropical and subtropical regions, with its transmission dynamics being influenced by both environmental factors and human mobility. The Dominican Republic, a biodiversity hotspot in the Caribbean, has experienced recurrent dengue outbreaks, yet detailed understanding of the virus's transmission pathways and the impact of climatic factors remains limited. This study aims to elucidate the recent transmission dynamics of the dengue virus (DENV) in the Dominican Republic, utilizing a combination of genomic sequencing and epidemiological data analysis, alongside an examination of historical climate patterns. Methods: We conducted a comprehensive study involving the genomic sequencing of DENV samples collected from patients across different regions of the Dominican Republic over a two-year period. Phylogenetic analyses were performed to identify the circulation of DENV lineages and to trace transmission pathways. Epidemiological data were integrated to analyze trends in dengue incidence and distribution. Additionally, we integrated historical climate data spanning several decades to assess trends in temperature and their potential impact on DENV transmission potential. Results: Our results highlight a previously unknown north–south transmission pathway within the country, with the co-circulation of multiple virus lineages. Additionally, we examine the historical climate data, revealing long-term trends towards higher theoretical potential for dengue transmission due to rising temperatures. Conclusion: This multidisciplinary study reveals intricate patterns of dengue virus transmission in the Dominican Republic, characterized by the co-circulation of multiple DENV lineages and a novel transmission pathway. The observed correlation between rising temperatures and increased dengue transmission potential emphasizes the need for integrated climate-informed strategies in dengue control efforts. Our findings offer critical insights for public health authorities in the Dominican Republic and similar settings, guiding resource allocation and the development of preparedness strategies to mitigate the impacts of climate change on dengue transmission.